Two new species of Infundibulicybe (Omphalinaceae, Agaricales) from northern China - Zhang, Yu-Xin; Mao, Ning; Li, Ting; Fan, Li (Phytotaxa, 2024)
Infundibulicybe confusa sp. nov. and I. phaeocentralis sp. nov. were described based on specimens from Shanxi Province in northern China. Morphologically, I. phaeocentralis is similar to I. rufa but the latter is differentiated by its isolated phylogenetic position and varied colors of the basidiomata. Infundibulicybe confusa is similar to I. alkaliviolascens, but I. alkaliviolascens has a pileus that turns violet to purplish pink in KOH and long basidiospores. Our morphological and phylogenetic analyses supported the taxonomic position of the two new species in Infundibulicybe. Additionally, a key to the species of Infundibulicybe in Shanxi Province is provided.